Phase connected X-ray light curve and He II radial velocity measurements of NGC 300 X-1. Issue Volume 14:Issue S346(2019) (August 2018) - Carpano, S.; Haberl, F.; Crowther, P.; Pollock, A.
Abstract: . NGC 300 X-1 and IC 10 X-1 are currently the only two robust extragalactic candidates for being Wolf-Rayet/black hole X-ray binaries, the Galactic analogue being Cyg X-3. These systems are believed to be a late product of high-mass X-ray binary evolution and direct progenitors of black hole mergers. From the analysis of Swift data, the orbital period of NGC 300 X-1 was found to be 32.8 h. We here merge the full set of existing data of NGC 300 X-1, using XMM-Newton, Chandra and Swift observations to derive a more precise value of the orbital period of 32.7932 ± 0.0029 h above a confidence level of 99.99%. This allows us to phase connect the X-ray light curve of the source with radial velocity measurements of He II lines performed in 2010. We show that, as for IC 10 X-1 and Cyg X-3, the X-ray eclipse corresponds to maximum of the blueshift of the He II lines, instead of the expected zero velocity. This indicates that for NGC 300 X-1 as well, the wind of the WR star is completely ionised by the black hole radiation and that the emission lines come from the region of the WR star that is in the shadow. We also present for the first time the light curve of two recent very long XMM-Newton observations of the source, performed on the 16th to 20th of December 2016.